Direct TiH2 powder production by the reduction of TiO2 using Mg in Ar and H2 mixed gas atmosphere - Sung-Hun Park; Junoh Oh; Youngju Song; Hyeong-Jun Jeoung; Jungshin Kang (Scientific Reports)
Abstract To develop a direct production process for TiH2 powder from TiO2, the reduction of TiO2 using Mg in molten MgCl2 – KCl salt under a high hydrogen chemical potential was investigated. The reduction of nano-sized TiO2 powder was conducted at 973 – 1073 K under an Ar or Ar and 10% H2 mixed gas atmosphere when the mass ratios of Mg to feed and salt to feed were 1.14 – 2.86 and 0.87 – 3.48, respectively. The results showed that the oxygen concentration in the Ti product decreased as the mass ratio of salt to feed and temperature decreased. Furthermore, according to the variation in Mg amounts, the oxygen concentration was 0.350 – 0.441 mass%. In addition, employing hydrogen during the reduction enhances the capability to decrease the oxygen concentration in the Ti product. Moreover, the hydrogen concentration in the Ti product increased as the amount of molten salt decreased, thereby enabling pure TiH2 production. As a result, TiH2 powder with an oxygen concentration of 0.350 mass% was obtained under a certain condition. These results demonstrate the feasibility of the direct production of low-oxygen TiH2 powder from TiO2 via reduction at 973 K using Mg in an Ar and H2 mixed gas atmosphere.